UPAYA DAN KENDALA PENGEMBANGAN MULTIMEDIA DALAM PEMBELAJARAN MATEMATIKA DI JURUSAN MATEMATIKA UNESA - Ismail, ; Atik Wintarti, ; Yuni Yamasari, ; Asma Johan, (Jurnal Penelitian Pendidikan Matematika dan Sains, 2008)
In learning and teaching mathematics, the use of multimedia is important in order to help students to understand mathematics topics. There are several competencies needed to develop multimedia in teaching mathematics, i.e. competencies in pedagogy, in mathematics content, in programming, and creativity. Therefore, the Mathematics Department of Unesa prepares its students by providing subjects such as: Teaching-Learning Process I-IV, School Mathematics I-II, Media in Learning teaching Mathematics, Computer Aplication and Visual Programming. Seminar of  Mathematics education and Skripsi are used to implement those subjects in the form of study report. In the second semester of year 2007/2008 some researches on development of multimedia in learning teaching mathematics have been held. The implementation results show that there are still a number of problems during the implementation of the multimedia.